Implementation of Parole in Prisoner Development in Correctional Institutions (Case Study at Class 1 Correctional Institution Surabaya) - Nurdiansyah, Eko; Yulianis, M. Sifa Fauzi; Samuji, Samuji (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Parole is one of the mechanisms in the criminal justice system that aims to reintegrate prisoners into society before their sentence ends, with certain conditions. This study aims to examine the implementation of parole in Class 1 Correctional Institution Surabaya, focusing on implementation and its challenges. The research method used is quantitative descriptive with an empirical juridical approach involving observation, in-depth interviews with inmates and prison officers, and analysis of related documents. The study results show that the implementation of parole in the Class 1 Prison in Surabaya has been going well and by applicable regulations. However, this study also found several obstacles, such as the absence of a guarantor as a condition for the implementation of parole, community resistance, the unpreparedness of the inmates themselves, and the factor of administrative completeness. In conclusion, although parole in the Class 1 Prison in Surabaya has been running well and its implementation has been in accordance with applicable regulations, its implementation requires improvements in terms of socialization to the guarantor and the community, and coordination between institutions is further improved. The recommendations of this study are increased training for prison officers, increased cooperation with community organizations, and the formulation of policies that are more supportive of the parole program.